Неорганические солевые расплавы в органическом синтезе. Технология производства водорода и синтез-газа - Гликин, М. А.; Тарасов, В. Ю.; Гликина, И. М.; Зубцов, Е. И. (НТУ "ХПИ", 2006)
Розглянуто техніко-економічні показники піролізу природного газу в реакторі з рідким високотемпературним теплоносієм. Досягнуто вміст водню в пірогазі 85 % об. Вивчена кінетика піролізу природного газу. Експериментально підтверджено можливість заміни багатостадійного виробництва водню конверсією природного газу на піроліз та зниження енерговитрат в 2 рази.

Technical and economic parameters of natural gas pyrolysis reactor in liquid high-temperature heat carrier are represented. The hydrogen concentration in gas of pyrolysis approximately 85 % vol. is achieved .The kinetics of natural gas pyrolysis is studied. The possibility of multistage technologies of hydrogen production by natural gas conversion replacement to pyrolysis and expenses of energy reduction in 2 times is experimentally confirmed.
Keywords: природный газ; легкие углеводороды; паровая конверсия метана; автотермический риформинг; парциальное окисление